"We live and we do this work": Women waste pickers' experiences of wellbeing in Ahmedabad, India. (April 2021) - Wittmer, Josie
Highlights: The study highlights relational aspects of physical, mental, social, and spiritual wellbeing. Waste picking flows across physical and social spaces, intersecting various roles and burdens. Precarious material, social, and spiritual assets enable woman waste pickers' everyday work. Women with multiple marginalized identities experience particular challenges to wellbeing. Marginalized workers pursue meaning-making and dignity despite constraining circumstances. Abstract: This study explores women waste pickers' perceptions and embodied experiences of wellbeing in Ahmedabad, India. Waste pickers are self-employed urban workers who collect and sell recyclable materials on an informal basis and experience an array of hazards, risks, stigmas, and exclusions in their everyday lives and livelihoods. The paper uses a fluid and multidimensional approach in understanding marginalized women workers' wellbeing as relational, intersectional, and situated. The paper grounds its conceptualization of wellbeing in respondents' occupational narratives and highlights the need for the hazardous conditions of this precarious livelihood to be understood in terms of women's own relational priorities and intersectional identities. This study is based on a survey (n = 401), semi-structured interviews (n = 45), follow-up visits (n = 36), and a series of group workshops (n = 12) with women waste pickers in Ahmedabad between 2016 and 2018. I engage a grounded and feminist approach, privileging women's lived experiences as central in conceptualizing and addressing wellbeing in research and practice. Research findings engage with the overlapping and multiple dimensions comprising respondents' everyday livelihood experiences, priorities of a 'good life, ' and experiences of physical, mental, social, and spiritual wellbeing. The paper argues that by focusing on women waste pickers' relational perceptions and priorities of wellbeing, we can understand waste picking work as an important asset for women in navigating everyday life and precarity in the urban margins. The study thus foregrounds women waste pickers' understandings of the benefits and importance of this livelihood and discusses implications of these findings in the context of broader structural oppressions, constraints, and changes to urban governance that inform respondents' everyday exclusions in various urban spaces and contexts.